1975
DOI: 10.2307/1589185
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Infectious Bursal Agent and Several Avian Adenoviruses in the Hemorrhagic-Aplastic-Anemia Syndrome and Gangrenous Dermatitis

Abstract: The effect that breeder-flock immune status regarding the infectious bursal agent (IBA) and two avian adenoviruses (DPI-1 and DPI-2) has on the susceptibility of their commercially reared Delmarva broiler progeny to the hemorrhagic-aplastic-anemia syndrome and concurrent gangrenous dermatitis was determined. Lack of immunity to the IBA in breeder flocks was related to an increased susceptibility of progeny to anemia and dermatitis. Breeder-flock immunity to the two adenoviruses tested could not be related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Thus examination of livers from natural cases of IBH have revealed either very few or no virus particles in the inclusions (Bickford et al, 1973;Howell et al, 1970;McCracken and McFerran, unpublished observations;Pettit and Carlson, 1972), whereas examination of livers from adenovirus induced hepatitis has shown cells with numerous adenovirus-like particles (Bickford et al, 1973;McCracken and McFerran, unpublished observations;Nakamatsu et al, 1968) similar to those described for chicken kidney cells infected with the eight prototype Japanese serotypes (Maeda et al, 1967). Rosenberger et al (1975) demonstrated that lack of immunity to infectious bursal disease in breeder flocks was related to an increased susceptibility of their progeny to anaemia and dermatitis. They postulated that chicks devoid of maternally derived antibody would be susceptible to infectious bursal disease virus infection in the first weeks of life, and the resulting immuno-suppression would allow the adenoviruses to produce the haemorrhagic-aplastic-anaemia syndrome.…”
Section: Inclusion Body Hepatitis In Fowlmentioning
confidence: 99%
“…Thus examination of livers from natural cases of IBH have revealed either very few or no virus particles in the inclusions (Bickford et al, 1973;Howell et al, 1970;McCracken and McFerran, unpublished observations;Pettit and Carlson, 1972), whereas examination of livers from adenovirus induced hepatitis has shown cells with numerous adenovirus-like particles (Bickford et al, 1973;McCracken and McFerran, unpublished observations;Nakamatsu et al, 1968) similar to those described for chicken kidney cells infected with the eight prototype Japanese serotypes (Maeda et al, 1967). Rosenberger et al (1975) demonstrated that lack of immunity to infectious bursal disease in breeder flocks was related to an increased susceptibility of their progeny to anaemia and dermatitis. They postulated that chicks devoid of maternally derived antibody would be susceptible to infectious bursal disease virus infection in the first weeks of life, and the resulting immuno-suppression would allow the adenoviruses to produce the haemorrhagic-aplastic-anaemia syndrome.…”
Section: Inclusion Body Hepatitis In Fowlmentioning
confidence: 99%
“…IBDV infects young chickens through the digestive tract and massively destroys B cells in the bursa of Fabricius, a primary lymphoid organ, causing immunosuppression and death. Surviving birds are severely immunocompromised and more susceptible to other avian pathogens (38). IBDV is therefore of major concern in the poultry industry.…”
mentioning
confidence: 99%
“…Clostridia may also contribute to other conditions in poultry under certain circumstances. Thus, Clostridium perfringens has been reported to cause necrotic enteritis (Parish, 1961) and has been isolated along with some aerobic bacteria from gangrenous dermatitis (Rosenberger et al, 1975;Cullen & Pattison, 1980;Milakovic-Novak et ah, 1984). Other reports of clostridial involvement in poultry diseases include C: perfringens type A (Al-Sheikhly & Truscott, 1977;Nillo, 1976), Clostridium novyi (Peterson, 1964), Clostridium sporogenes (Peterson, 1967), Clostridium septicum (Fowler & Hussaini, 1975) and Clostridium fallax (Ellwood & Halliwell, 1973).…”
Section: Discussionmentioning
confidence: 99%